Studi Pengaruh Paparan Debu Dan Karakteristik Individu Terhadap Gangguan Faal Paru Pekerja Pt. X - Ahmad Erlan Afiuddin, Nur Ifrah Rohadul Aisy, Am Maisarah Disrinama (Techno Bahari, 2016)
X is a company engaged in the production of fertilizers and chemicals. The process that occurs in the PT. X always produce dust, dust measurements that exceed the threshold limit value contained in one location that is the place of production and storage 29 mg/m3. Based on the secondary data that results of the company in 2008 till the 2010 obtained an increase in the number of disorders below normal lung function annually. Sampling based on stratified random sampling as many as 28 out of 50 people, data collection is done by filling in questionnaires and interviews to identify the individual characteristics of fiber dust exposure measurement and inspection capacity lung physiology function. Data were analyzed by chi square test (X2) and logistic regression Binner with SPSS version 20. The results of measurements of exposure to total dust inhaled by workers is below the threshold limit value of 16 respondents and exposure to dust above the threshold limit value as much as 12 respondents. And the results of the examination of workers pulmonary function function capacity of 28 respondents as many as 12 respondents are not impaired lung function, 16 respondents impaired lung function. Based on the results of chi square test showed that exposure and long exposure to the dust has a significant relationship to lung function disorders, whereas individual characteristics that affect the lung function disorders are age, nutritional status and smoking habits. based on Logistic regression analysis showed that exposure to dust Binner terhdadap ganggual influence lung function, and individual characteristics that affect the lung function disorders are age, length of employment, nutritional status and smoking habits.